Omni-directional caster drive development for automating a hospital bed transport system - Han, Yi Chou (2019)
Healthcare as we know it is becoming more advanced and the average human lifespan is increasing. With the trend of ageing population becoming more prominent, there is a shortage of trained healthcare professionals in the market. This project aims to alleviate this by introducing a concept that aids the declining pool of healthcare professionals in their daily laborious routines, freeing their time up for more skill intensive tasks. This report explains the reason for embarking on this project, the process of designing the prototype, and the verification methods used to ensure the project has met its intended objectives.